2016
DOI: 10.3389/fped.2016.00130
|View full text |Cite
|
Sign up to set email alerts
|

Preterm Birth during Influenza Season Is Associated with Adverse Outcome in Very Low Birth Weight Infants

Abstract: ObjectiveWe investigated the relationship between influenza seasonality and outcome of very low birth weight infants (VLBWI) in a large observational cohort study of the German Neonatal Network.Materials and methodsWithin the observational period (July 2009 until December 2014), five influenza seasons occurred (mean duration: 97 days, range: 48–131 days). We stratified VLBWI (n = 10,187) according to date of birth into three categories: (1) before influenza season, (2) during influenza season, and (3) 3 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Both seasonal and pandemic influenza virus have a substantial impact on the developing fetus. Infection during late-second or third trimester of pregnancy is associated with significant increases in miscarriages, stillbirths, and early neonatal diseases and death [ 1 , 11 ]. Several studies indicate that infants born to influenza virus-infected mothers have an increased risk of developing health problems later in life ranging from chronic immune diseases to schizophrenia [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both seasonal and pandemic influenza virus have a substantial impact on the developing fetus. Infection during late-second or third trimester of pregnancy is associated with significant increases in miscarriages, stillbirths, and early neonatal diseases and death [ 1 , 11 ]. Several studies indicate that infants born to influenza virus-infected mothers have an increased risk of developing health problems later in life ranging from chronic immune diseases to schizophrenia [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…These reports demonstrated adverse effects of the 2009 pandemic influenza A (H1N1) virus on lung immunopathology [ 25 27 ], and more recently Kim et al reported severe pathogenesis of influenza B virus in the pregnant mouse model. However, the impact of seasonal H1N1 influenza A virus infection on maternal and fetal health during pregnancy, and the exact mechanisms leading to premature rupture of membranes (PROM) and preterm birth after influenza virus infection during pregnancy have not been fully elucidated [ 6 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The outbreaks of certain infections are named according to the causative microorganisms (e.g., “RSV season”, “influenza season”). Certain seasons may vary due to climatic conditions year after year, but usually most are recognised to occur from October to April in the Northern hemisphere ( 7 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…The fetus can experience adverse outcomes on influenza infection of the mother. Severe infections are associated with preterm delivery, increased rates of stillbirth, and low birth weight (Kim et al 2014;Härtel et al 2016;Oboho et al 2016;Fell et al 2017;Littauer et al 2017). Influenza can infect fetal-related tissues, with infections of the maternal decidua of the greatest likelihood to support active viral replication (Takeyama 1966;Rosztoczy et al 1975;McGregor et al 1984;Uchide et al 2006).…”
Section: Pregnancymentioning
confidence: 99%